Thermal behavior (TG-DTA-TMA), sintering and properties of a kaolinitic clay from Buenos Aires Province, Argentina - Conconi,M. S. (2019)
Abstract The technological properties of a local kaolin, considered as a potential industrial material, were correlated with the thermal behavior and sintering processes carried out through a series of thermochemical analyses. The chemical and mineralogical characterization of the material was carried out, together with a simple microstructural characterization. The used material corresponded to the kaolinized basement rocks (saprolite zone) mined at La Verónica quarry, Chillar area, Azul County, Argentina. The complete kaolinite-metakaolinite-spinel-mullite thermal series was characterized. Sintering behavior was studied; a viscous phase sintering mechanism was proposed. Apparent density and porosity of fired ceramics were measured. A light-firing color was confirmed by colorimetry. The viscous phase mechanism was possibly described thanks to the multi-technique thermal behavior analysis complemented by XRD analysis. These results permitted to establish formulation and processing strategies of ceramic materials based on the studied clay. The possible applications include: tile manufacturing, sanitary ware, tableware, kaolinitic proppants, chamotte and refractory materials.